Physical exercise programs at Basic Healthcare Units decrease body fat and improve the functional capacity of women over 50 years old - Rossi, Fabrício Eduardo; Lecca, Anderson Rogério; Martins, Luiz Gustavo Perón; Takahashi, Luciana Sanae Ota; Christofaro, Diego Giuliano Destro [UNESP]; Gobbo, Luís Alberto [UNESP]; Freitas, Ismael F. [UNESP] (Korean Society of Exercise Rehabilitation, 2017)
This study verified the effects of a physical exercise program performed at Basic Healthcare Units on the body composition and functional capacity of women over 50 years old and to compare these variables according to age. Forty-eight women (age, 65.4± 7.3 years) were assessed. The program lasted 20 weeks, and was conducted 2 times per week, 60 min/day. Body mass and height were collected and body mass index (BMI) was calculated. Bioelectrical impedance was used to estimate fat mass and fat free mass. Functional capacities: handgrip test, Timed Up and Go (TUG) test, and Guralnick test were assessment. Weight (68.7± 12.5 [pre]× 66.8± 12.5 [post], P < 0.001), BMI (28.5± 4.1 kg/ m2 [pre]× 27.6± 4.0 kg/m2 [post], P < 0.001), and fat mass (28.4± 7.8 kg [pre]× 26.4± 7.3 kg [post], P < 0.001) were decreased. For functional capacity, handgrip (21.2± 5.8 kg [pre]× 22.9± 6.9 kg [post], P= 0.014), lower limb strength (12.0± 3.0 sec [pre]× 8.5± 2.2 sec [post], P < 0.001), TUG (8.4 ±1.5 sec [pre] ×7.6 ±1.1 se [post], P < 0.001) and Guralnik tests (10.6± 1.6 [pre]× 11.8± 0.5 [post], P < 0.001) were improved. 20 weeks of exercise program performed at Basic Healthcare Units decreased body fat and improvement of functional capacity of women over 50 years old and there was difference according to age only on the body composition variables.
Keywords: Elderly; Exercise; Health care